Treatment outcomes of a CBT-based group intervention for adolescents with Internet use disorders - Szász-Janocha, Carolin; Vonderlin, Eva; Lindenberg, Katajun (Journal of behavioral addictions, 2020)
Abstract Background and aims: Instances of Internet use disorders (IUD) including Internet gaming disorder (IGD) and non-gaming pathological Internet use (ng-PIU) have the extent that they are now a growing mental health issue. Individuals suffering from IUD show a large range of symptoms, high comorbidities and impairments in different areas of life. To date there is a lack of efficient and evidence-based treatment programs for such adolescents. The present registered single-arm trial (ClinicalTrials.gov:NCT03582839) program for adolescents with IUD. Methods N = 54 patients (16.7% female), aged 9-19 years M = 13.48, SD = 1.72) received the CBT group program PROTECT+. IUD symptom severity (primary outcome variable) as well as comorbid symptoms, risk-related variables and potentially protective skills (secondary outcome variables) were assessed at pretest, posttest, as well as 4 and 12 months after admission. Results Patients showed a significant reduction in IUD symptom severity at the 12-month follow-up. Effect sizes were medium to large depending on the measure. Beyond the statistical significance, the clinical significance was confirmed using the reliable change index. Secondary outcome variables showed a significant reduction in self-reported depression, social anxiety, performance anxiety and school anxiety as well as in parental-reported general psychopathology. Discussion and conclusions The present study shows long-term effects of a manual-based CBT treatment for adolescents suffering from IUD. The results indicate that even a 4-session brief intervention can achieve a medium to large effect over 12 months. Future work is needed to confirm the efficacy within a randomized controlled trial (RCT).
Gesehen am 23.02.2021